Etika Bisnis Islam Dalam Pengendalian Persediaan Material Pada Pabrik PT Sawit Inti Raya - Pidola, Viras Alti; Arfah; Fairus, Imam (Yayasan Darussalam Patalassang, 2025)
From the perspective of Islamic business ethics, behavior in the business world must align with the teachings of the Qur'an. The purpose of this study is to examine Islamic business ethics in the implementation of control systems at PT. SIR (Sawit Inti Raya) to achieve inventory cost efficiency. This research uses a qualitative approach, with the research subjects being employees at PT Sawit Inti Raya, located in Bongkal Malang Village, Kelayang District, Indragiri Hulu Regency, Riau Province. The analysis results show that the volume of incoming and outgoing goods is relatively balanced, indicating a fairly stable inventory management system. The main challenge in material management is ensuring that stock is available without shortages or surpluses. Effective inventory management can optimize the availability of goods and reduce the risk of errors that could harm the company. Organized arrangement and storage of goods in the warehouse greatly contribute to stock control and support the smooth operation of activities at PT Sawit Inti Raya.